2012
DOI: 10.3389/fphys.2012.00317
|View full text |Cite
|
Sign up to set email alerts
|

Application of in vitro bioaccessibility and bioavailability methods for calcium, carotenoids, folate, iron, magnesium, polyphenols, zinc, and vitamins B6, B12, D, and E

Abstract: A review of in vitro bioaccessibility and bioavailability methods for polyphenols and selected nutrients is presented. The review focuses on in vitro solubility, dialyzability, the dynamic gastrointestinal model (TIM)™, and Caco-2 cell models, the latter primarily for uptake and transport, and a discussion of how these methods have been applied to generate data for a range of nutrients, carotenoids, and polyphenols. Recommendations are given regarding which methods are most justified for answering bioaccessibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
264
1
23

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(288 citation statements)
references
References 193 publications
0
264
1
23
Order By: Relevance
“…This cell line derived from colonic adenocarcinoma surprisingly well mimics intestinal cell behaviour upon long culture. The fortnight culture of these cells on porous membranes of inserts leads to the creation of an impervious epithelial layer of polarized cells which resemble mature enterocytes (27). Tissue culture tests provide a relatively quick and cost-eff ective tool for predicting the absorption of bioactive components by assessing the probability of their transport through epithelial layer (28).…”
Section: Resultsmentioning
confidence: 99%
“…This cell line derived from colonic adenocarcinoma surprisingly well mimics intestinal cell behaviour upon long culture. The fortnight culture of these cells on porous membranes of inserts leads to the creation of an impervious epithelial layer of polarized cells which resemble mature enterocytes (27). Tissue culture tests provide a relatively quick and cost-eff ective tool for predicting the absorption of bioactive components by assessing the probability of their transport through epithelial layer (28).…”
Section: Resultsmentioning
confidence: 99%
“…A limitation of in vitro iron solubility experiments is that they greatly oversimplify the highly complex physicochemical and physiologic events underlying human digestion (33). Thus, in vitro solubility may provide qualitative, but not quantitative, information on potential bioavailability (34) and measurements in vivo are more likely to mimic the true interactive effects of zinc on iron bioavailability from fortified rice (35).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Mn bioaccessibility in the lettuce (Lactuca sativa L.) leaves decreased in the order of gastric > residual > intestinal [98], while [99] revealed that the solubility of Cd in the cock's comb (Celosia argentea L.) followed the order gastric > residual > intestinal. The bioaccessibility of metals from the different digestion phases is dependent on several factors such as the digestion and release of the ingested food matrix [100].…”
Section: First-second-third-fourth Phasesmentioning
confidence: 99%